Essential Heavy Metals in Renal Tumor Tissue and Its Possible Relation to Carcinogenesis: Applying the Scanning Electron Microscopy Coupled with X-Ray Microanalysis Technique - Tânia Nogueira; Mariana Semedo; Elisabete Cunha (International Journal of Medical Students, 2015)
Background: Metals such as copper and zinc are crucial in several vital functions in the human body; the absence of these metals can cause serious illness. When in excess, however, they can have toxic effects which may be associated with carcinogenesis, as is described in the literature. Thus, it is important to realize that without these essential metals in their due proportion, the human body could not maintain its proper metabolic function. Methods: The main goal of this paper was to compare qualitatively and semi-quantitatively the amount of both copper and zinc present in the tumor tissue (tissue from patients who had undergone partial or radical nephrectomy) andin the control tissue (which was adjacent to the tumor tissue). This study was carried out using Scanning Electron Microscopy coupled with X-Ray Microanalysis (SEM-XRM). Results: There is a different concentrations of copper and zinc in the samples of tumor tissue and controls that were studied. Conclusion: This work complements previously published results about the presence of metals in the human body and their probable influence on carcinogenesis